Marketable Incentive Contracts and Capital Structure Relevance - GARVEY, GERALD T. (Journal of Finance, 1997)
ABSTRACT This article investigates the claim that debt finance can increase firm value by curtailing managers' access to “free cash flow.” We first show that incentive contracts that tie the managers' pay to stockholder wealth are often a superior solution to the free cash flow problem. We then consider the possibility that the manager can trade on secondary capital markets. Liquid secondary markets are shown to undermine management incentive schemes and, in many cases, to restore the value of debt finance in controlling the free cash flow problem.